Use of XR to revitalize and activate shop windows - Karin Kueffmann (ZBW - Leibniz Information Centre for Economics, 2024)
Virtual and augmented reality (VR/AR) that can be applied in many ways. A number of innovative immersive applications have already been created online commerce and in real retail. More VR/AR applications can be found in the fields of arts, fashion, real estate, architecture, city planning and guided tours. In this paper a concept for the use of AR or VR for vacant spaces in a formerly attractive shopping street is presented. In addition to common technologies and interoperability, the focus lies on revitalisation, interaction and networking of existing actors in a district. The vacancies should be brought to life with XR in a technologically and thematically diverse way, if possible as a participatory concept for many stakeholders, and thus contribute to the revitalisation of the district. – – VR / AR wird heute in vielfältiger Weise im Online-Handel, in der Architektur, Immobilienwirtschaft, im Maschinenbau und in der Stadtplanung verwendet. Im folgenden wird untersucht, ob Mixed Reality eine Chance ist, Schaufenster wieder lebendiger werden zu lassen und so Leerstände zu beleben.
Additional information: Shortened translation into English of Küffmann, Karin: Einsatz von XR zur Belebung von Leerständen. HMD Praxis der Wirtschaftsinformatik (2023). https://doi.org/10.1365/s40702-023-01020-9
Keywords: 330; Virtual Reality; Augmented Reality; empty shop windows; inner city; retail; activation in showrooms; co content creation; mixed reality; living neighbourhood; urban development